Recent Developments of Cathode Materials for Thermal Batteries - Li, Renyi; Guo, Wei; Qian, Yumin (Frontiers in Chemistry, 2022)
Big progress has been made in batteries based on an intercalation mechanism in the last 20 years, but limited capacity in batteries hinders their further increase in energy density. The demand for more energy intensity makes research communities turn to conversion-type batteries. Thermal batteries are a special kind of conversion-type battery, which are thermally activated primary batteries composed mainly of cathode, anode, separator (electrolyte), and heating mass. Such kinds of battery employ an internal pyrotechnic source to make the battery stack reach its operating temperature. Thermal batteries have a long history of research and usage in military fields because of their high specific capacity, high specific energy, high thermal stability, long shelf life, and fast activation. These experiences and knowledge are of vital importance for the development of conversion-type batteries. This review provides a comprehensive account of recent studies on cathode materials. The paper covers the preparation, characterization of various cathode materials, and the performance test of thermal batteries. These advances have significant implications for the development of high-performance, low-cost, and mass production conversion-type batteries in the near future.